The Effect of Tax Literacy, Taxpayer Awareness, and Tax Sanctions on Compliance with OP Annual SPT Submission - Ventje Jeffry Kuhuparuw; Ardiansyah Ardiansyah; Laura Stefany Nunumete (Budapest International Research and Critics University, 2022)
The purpose of this study is to empirically examine the effect of tax literacy, taxpayer awareness, and tax sanctions on compliance with the submission of annual tax returns for WP OP for employees at Manise Hotel and Swiss-belhotel Ambon. The two hotels are respectively 3 and 4 stars which are considered representative of the hotel population in Ambon City, Maluku Province. Therefore, this research is applied research that conducts an empirical study and has never done similar research before. Research data collection was carried out in 2022.The findings in this study prove that: (1) Tax literacy has a positive and significant effect on compliance with the submission of the Annual Tax Return of WP OP; (2) Taxpayer awareness has a positive and significant impact on compliance with the submission of the Annual Tax Return for WP OP; (3) Tax sanctions have a positive and significant effect on compliance with the submission of the Annual Tax Return of WP OP; and (4) tax literacy, taxpayer awareness, and tax sanctions have a simultaneous effect on compliance with the submission of the Annual Tax Return of WP OP. All hypotheses proposed in this study were accepted. The implications of this research are for hotel management in Ambon City and KPP Pratama Ambon in order to improve assistance, socialization, and training to hotel employees according to the principle of the self-assessment system because it is proven that the higher tax literacy and awareness of taxpayers, the more compliance with the submission of OP Annual SPT. As for tax sanctions, they must continue to be socialized in various electronic media which are currently developing very rapidly because it is empirically proven to have a higher coefficient value compared to tax literacy and taxpayer awareness of compliance with the submission of Annual Tax Returns for WP OP means social. The socialization of tax sanctions is far more effective than socialization to instill awareness in taxpayers. Nevertheless, both of these things must still be given education to WP.